Integration of Multiple Mechanical Stimuli in the Lamprey Central Pattern Generator - Phan, Annie (Tufts Archival Research Center, 2020)
In vertebrates, rhythmic movements such as undulatory swimming are generated by groups of interneurons in the spinal cord called central pattern generators (CPGs), which are sensitive to sensory inputs. When a rhythmic stimulus is applied, CPGs are known to adjust their output frequency to match the frequency of a the stimulus and maintain a stable phase offset with it, a process called entrainment. Previous studies have characterized CPG entrainment with forced motion at one end only, which does not resemble normal swimming. This study aims to understand how the CPG integrates multiple bending stimuli, which is more comparable to what the spinal cord would normally receive. To do so, the spinal cord and notochord were isolated from a lamprey and bent at either the rostral or caudal end, then both at the same time with different phase offsets between the two stimuli. Action potentials in the ventral roots were recorded to determine the range of stimulus frequency over which entrainment took place. In the lamprey spinal cord with no mechanical stimuli, the motor outputs of CPGs alternate left and right and have a natural intersegmental delay of 1% of a cycle per segment in the rostral to caudal direction. We hypothesized that bending at both ends may yield a larger entrainment range than bending at one end since the combined amplitude, and hence the intensity of the bending signal, is greater. We also hypothesized that when the phase offset of the applied bending matches the natural phase lag of the spinal cord, we would measure the largest entrainment ranges. Results suggested significant difference in entrainment ranges between caudal only bending and rostral only bending, and between double bending and rostral only bending, but not between double bending and caudal only bending. Levels of entrainment ranges were also widely distributed across all phase offsets rather than in a predictable pattern. Advisor: Dr. Eric D. Tytell.